Relative shrinkage of adipocytes by paraffin in proportion to plastic embedding in human adipose tissue before and after weight loss - Verhoef, Sanne P.M.; van Dijk, Paul; Westerterp, Klaas R. (Obesity research & clinical practice, 2013)
Adipocyte size is a major modulator of endocrine functioning of adipose tissue and methods allowing accurate determination of adipocyte size are important to study energy metabolism. The aim of this study was to assess the relative shrinkage of adipocytes before and after weight loss by comparing adipose tissue from the same subjects embedded in paraffin and plastic. 18 healthy subjects (5 males and 13 females) aged 20–50 y with a BMI of 28–38kg/m2 followed a very low energy diet for 8 weeks. Adipose tissue biopsies were taken prior to and after weight loss and were processed for paraffin and plastic sections. Parameters of adipocyte size were determined with computer image analysis. Mean adipocyte size was smaller in paraffin compared to plastic embedded tissue both before (66±4 vs. 103±5μm, P<0.001) as after weight loss (62±4 vs. 91±5μm, P<0.001). Relative shrinkage of adipocytes in paraffin embedded tissue in proportion to plastic embedded tissue was not significantly different before and after weight loss (73 and 69%, respectively). Shrinkage due to the type of embedding of the adipose tissue can be ignored when comparing before and after weight loss. Plastic embedding of adipose tissue provides more accurate and sensitive results.